2014
DOI: 10.4238/2014.march.12.6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of porcine circovirus type 2 and pseudorabies vaccine co-inoculation on regulatory cytokine mRNA expression in pig peripheral blood mononuclear cells

Abstract: ABSTRACT. We investigated the immune response effects of porcine circovirus type 2 (PCV2) on cells inoculated with pseudorabies attenuated vaccine (PRV). Real-time PCR was used to detect the mRNA expression levels of the regulatory cytokines IL-4, IL-10, IL-12p40, and IFN-γ in pig peripheral blood mononuclear cells, after in vitro single vaccination and co-inoculation with PCV2 and the PRV. We found that PRV causes upregulation of IL-4, IL-12p40, and IFN-γ mRNA expression, while PCV2 causes mRNA upregulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…PCV2 infection can downregulate immune cell function during recall antigen responses, and induce IL-10 secretion by monocytic cells, leading to effective repression of IL-12 in PBMCs [103,104]. PRV-induced IFN-α secretion, IL-4 and IL-12p40 upregulation, and IFN-γ expression are also inhibited by PCV2 infection [103,105]. Moreover, PRV was repressed by subsequent PCV2 infection [104].…”
Section: Co-infection Of Pcv2 With Other Swine Virusesmentioning
confidence: 99%
“…PCV2 infection can downregulate immune cell function during recall antigen responses, and induce IL-10 secretion by monocytic cells, leading to effective repression of IL-12 in PBMCs [103,104]. PRV-induced IFN-α secretion, IL-4 and IL-12p40 upregulation, and IFN-γ expression are also inhibited by PCV2 infection [103,105]. Moreover, PRV was repressed by subsequent PCV2 infection [104].…”
Section: Co-infection Of Pcv2 With Other Swine Virusesmentioning
confidence: 99%
“…In this previous study, PCV2 significantly inhibited the ability of inactivated PRV to induce IFN-γ expression. The authors suggested that PCV2 could affect the cell immune response to PRV [69]. In the context of the present study, it is believed that the impaired IFN response observed in PCV2b persistently infected iPAM 3D4/21 cells could favor SwIV infection and replication.…”
Section: Discussionmentioning
confidence: 53%
“…In iPAM 3D4/21 co-infected cells, PCV2b completely impaired the modulation of the transcriptional expression of IFN-β and IFN-γ by SwIV. Gao et al (2014) have reported a similar PCV2 effect on IFN expression during dual infection with pseudorabies virus (PRV) in PBMC [69]. In this previous study, PCV2 significantly inhibited the ability of inactivated PRV to induce IFN-γ expression.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Evaluating immune mediators, such as cytokines and related lymphocyte subpopulations involved in the immune response, can contribute to understanding the efficiency of host immune responses to vaccines and the subsequent immunoprotection. Innate proinflammatory (TNF-a, IL-1b, IL-8) and adaptive immune (IFN-c, IL-10) cytokines are thought to be related to the viral load and the presence of clinical signs of PMWS (13,25). IFN-c is usually produced by host cells during adaptive response to a vaccine or virus and can effectively resist viral replication and activate NK cells to clear the virus (11,23).…”
Section: Discussionmentioning
confidence: 99%